PEMBELAJARAN MANAJEMEN RESIKO DALAM KETRAMPILAN BAHASA DAN BUDAYA BAGI PESERTA PROGRAM INTERNASIONAL - Aniroh, Kun (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
Risk management theoritically or practicallyis an important need for the international program particpants and for the organizer.Many campuses in Indonesia hold the Indonesian Language and Culture Program and other similarcultural programs.To face the enaction of ASEAN Economic Community next December 2015 in which one of the programs is the issuance of free visa for skilled labors, the international exchange for studying, apprenticeship, and working is becoming more intensive due to the fact that Indonesia is a potential market and is an attractive tourist destination.Therefore, risk management is a compelling need. The success of managing risk for the safety of international program participants can enhance the image of Indonesia in education, tourism, trade and other sectors. Based on the importance of risk management in including it in the language and culture skill or other similar programsin Indonesian and English as the best parctice,it is hoped to contribute in the education of minimizing disaster risks.